As dificuldades e desafios da educação ribeirinha: uma história de superação - Torres, Maria da Conceição Campelo da Silva (Brasil, 2024)
This work addresses the difficulties faced in education in riverside regions, highlighting the unique challenges that educators and students face in this context. It is divided into three chapters that each explore a different context. In the first, it brings memories of how my first readings took place at school and tells a little about the memorial that was built throughout the Pedagogy course. This also tells how I entered teaching, a career that I embraced and continue to pursue with responsibility and love. In the second chapter it discusses how I entered Higher Education, overcoming the difficulties in this process and the adventures experienced during these years of course and in the third chapter it presents the experiences lived in the internships that were carried out both in the classroom and in school management. Finally, I bring my final considerations on how enriching this adventure of knowledge was, as well as the references from authors that we used in the body of this academic work.